Little dimension and the improved new intersection theorem - Nakamura, Tsutomu; Takahashi, Ryo; Yassemi, Siamak (Mathematica Scandinavica, 2020)
Let R be a commutative noetherian local ring. We define a new invariant for R-modules which we call the little dimension. Using it, we extend the improved new intersection theorem.